Appointment of Leader Position: Study on the Regional Government of West Nusa Tenggara - Anwar, Raihan; Luddin, Muchlis Rantoni; Wibowo, Agus (Indonesian Journal of Social Science Research, 2021)
This study aims to develop a model for leadership appointment positions in the Regional Government of Nusa Tenggara Barat. Using Yin multi case study method, data collection was carried out through observation, tracing and document analysis as well as in-depth interviews with informants consisting of two clusters (K-I and K-II). This research found that competence supports meritocracy, because the higher the competence, the better the meritocracy value. Meritocracy get the most dominant element, and political intervention has a negative role on employees and hinders the implementation of meritocracy, however, political functions in policy formulation and political control over the bureaucracy are needed. Local wisdom strengthens values ​​of morality and integrity so as to fortify the unfair competition between civil servants and the discretion of regional heads. Talent management as urgent factor considering that more than half of the human resources are in a critical age. The study recommends developing a model for leadership appointment position with local wisdom and talent management elements that reinforce competence and meritocracy and inhibit political discretion towards superior performing leaders.